Impaction Due to Sharp-Shaped Trauma in the Thoracic Abdominal Region: A Case Report - Pertuz, José Gregorio Villa (Jour Med Resh and Health Sci, 2022)
Introduction: Cases in which impalement occurs have a very low incidence, especially those in which more than one anatomical region is involved. Objective presentation of the case: To present to the scientific community a case report about a case of impalement and its therapeutic behavior Presentation of the case: In the following report, the case of a 57-year-old patient who, after suffering an occupational accident, is pierced by an iron rod, thus causing left pneumothorax, ipsilateral diaphragm wound, who was managed in a multidisciplinary way, with satisfactory results for the patient. Conclusions: Cases of impalement will always be a challenge in terms of choosing the best therapeutic behavior, in the previous case it was evidenced as an integral management with a group of trained specialists, it could be reflected in the evolution of the patient.